Sentimen Masyarakat Terkait Perpindahan Ibukota Via Model Random Forest dan Logistic Regression - Martaliana Putri Agustina; Hendry Hendry (AITI, 2021)
This study aims to determine public opinion regarding the relocation of the capital of Indonesia. The pros and cons conveyed by the community are important because they can be constructive input for the government. The applications used to support the research are Orange and Twitter. The data obtained must go through several processes such as preprocess text, sentiment analysis, and testing algorithms to ensure data accuracy before making a decision tree. This research uses Random Forest and Logistic Regression as the research models. As for the results, Random Forest obtains higher accuracy value than Logistic Regression and it is considered that time did not affect the classification. The result obtained from the decision tree is that more people choose to have a neutral opinion on this program. People prefer to entrust everything to the government, because the government must have thought about the positive or negative impacts in the long term.